Uso subconjuntival de lipossomas com rapamicina e tacrolimus tópico no tratamento de ceratoconjuntivite seca em cães - Fonzar, Joice Furtado [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present study aimed to evaluate the use of the association of topical Tacrolimus with liposomes containing Rapamycin in dogs with severe keratoconjunctivitis sicca, non-responsive to conventional treatments. Were studied 29 eyes with Schirmer tear test value of less than 5 mm/min. The dogs received every 15 days a subconjunctival injection of liposomes with Rapamycin at a dose of 0.4 mg/ml for two months. Topical eye drop medication was maintained with 0.03% Tacrolimus. Complete ophthalmologic evaluation using a modified McDonald-Shadduck protocol, as well as Schirmer tear tests I and II and tear film break up time were made every 15 days. The treatment used did not cause ocular side effects in any animal studied. The association of topical Tacrolimus with liposomes containing Rapamycin was effective in alleviating the clinical signs of keratoconjunctivitis sicca in dogs, as well as increased tear production and tear film quality of the studied animals

O presente estudo teve por objetivo avaliar o emprego da associação de Tacrolimus tópico com lipossomas contendo Rapamicina, em cães com ceratoconjuntivite seca grave, sem resposta a tratamentos convencionais. Foram estudados 29 olhos com valor de teste lacrimal de Schirmer menor que 5 mm/minuto. Os cães receberam, a cada 15 dias, durante dois meses, injeção subconjuntival de lipossomas com Rapamicina na dose de 0,4mg/ml, sendo mantida a medicação tópica com colírio de Tacrolimus 0,03%. Avaliação ocular completa, utilizando-se do protocolo de McDonald e Shadduck modificado, bem como testes de produção lacrimal Schirmer I e II e tempo de ruptura do filme lacrimal, foram realizados a cada 15 dias. O tratamento empregado não gerou efeitos adversos oculares em nenhum animal estudado. A associação de Tacrolimus tópico com lipossomas contendo Rapamicina foi eficaz na atenuação dos sinais clínicos de ceratoconjuntivite seca em cães, bem como incrementou a produção lacrimal e a qualidade da lágrima dos animais tratados
Use of subconjunctivally injected liposome encapsulated rapamycin and topically administered tacrolimus for the treatment of keratoconjunctivitis sicca in dogs
Keywords: Cão - Doenças; Ceratoconjuntivite seca; Cornea - Doenças; Aparelho lacrimal - Doenças; Rapamicina; Tacrolimo; Lacrimal organs - Diseases